Neutron and X-Ray Reflectivity Studies of the Adsorption of Aerosol-OT at the Air-Water Interface: The Structure of the Calcium Salt - Li, Z; Lee, E; Thomas, R; Penfold, J (1997)
We have used neutron and X-ray reflection to determine the structure of a layer of calcium bis-(2-ethyl 1-hexyl) sulphosuccinate (Aerosol-OT or AOT) adsorbed at the air/solution interface. The widths of the distributions of the chains and head groups of the molecule, and their positions in relation to the underlying water, have been measured at four concentrations varying from the solubility limit (CMC) at 4 x 10(-4) M to 1 x 10(-6) M. Over this concentration range the coverage changes from 68 andplusmn; 3 to 142 andplusmn; 8 andAring;2 per AOT unit. The structure of the layer both is quite different from that of NaAOT and varies quite differently with surface concentration. The Ca(AOT)2 layer is slightly (1 andAring;) further out from the water, but the chain region is thinner for the calcium surfactant. This is reflected most in the greatly reduced chain to head separation, which drops from about 6 andAring; in NaAOT to about 4 andAring; in Ca(AOT)2.